Work-family conflict and job performance: moderating effect of social support among employees in Malaysian service sector - Zainal, Nurhafizah; Zawawi, Dahlia; Abdul Aziz, Yuhanis; Ali, Mass Hareeza (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2020)
This study aims to examine the relationship between work-family conflict (work interference family and family interference work) and job performance among employees in Malaysian service sector. In addition, this study focuses on exploring the moderating effect of social support received from supervisors and family members on the relationship of work-family conflict dimensions with employee’s job performance. This study is employed quantitative method whereby the questionnaires are used to gather the data.The data for the present study were collected from a total of 250 employees working in Malaysian service sector.The mean, standard deviations, correlations, and moderated hierarchical regression analysis were performed in analyzing the data by using the IBM SPSS statistics software 23. The results of the study indicate that work interference family and family interference work are negatively correlated with employee’s job performance. Moreover, social support received from supervisors and family members is observed to significantly moderate the relationship of work interference family and family interference work with employee’s job performance.